2017
DOI: 10.1016/j.apcata.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning of Ru/C by homogeneous Brønsted acids in hydrodeoxygenation of 2,5-dimethylfuran via catalytic transfer hydrogenation

Abstract: It has been proposed that the combination of metal and acid sites is critical for effective ring opening of biomass-derived furans to linear molecules, a reaction that holds promise for the production of renewable polymer precursors and alkanes. In this work, we use 2,5-dimethylfuran (DMF) as a model compound to investigate hydrogenolysis and hydrogenation pathways using a combination of H2SO4 and Ru-mediated catalytic transfer hydrogenation in 2-propanol. Acid-catalyzed hydrolytic ring opening of DMF to 2,5he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…HMF may be obtained by the dehydration of model compounds, including monosaccharides, such as glucose [8][9][10][11] and fructose [11][12][13][14][15], polysaccharides, such as inulin [12,13,16], starch [11,15] and cellulose [11,15,17,18] and, more advantageously, real lignocellulosic biomasses, such as corn stover, pinewood, switchgrass and poplar [14,19]. The presence of different reactive groups (an aldehyde group, a hydroxyl group and a furan ring) makes HMF a very important platform-chemical, precursor of bio-fuels, such as 2,5-dimethylfuran (DMF) [20,21], 5-ethoxymethylfurfural (EMF) [22] and long chain alkanes [23]. In addition, it is possible to convert HMF into interesting monomers, such as 2,5-furandicarboxylic acid (FDCA) [24,25], 2,5-bis (hydroxymethyl)furan (BHMF) [26][27][28], 2,5-bis(hydroxymethyl)tetrahydrofuran (BHMTHF) [29][30][31] and caprolactone [32] and many more valuable products [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…HMF may be obtained by the dehydration of model compounds, including monosaccharides, such as glucose [8][9][10][11] and fructose [11][12][13][14][15], polysaccharides, such as inulin [12,13,16], starch [11,15] and cellulose [11,15,17,18] and, more advantageously, real lignocellulosic biomasses, such as corn stover, pinewood, switchgrass and poplar [14,19]. The presence of different reactive groups (an aldehyde group, a hydroxyl group and a furan ring) makes HMF a very important platform-chemical, precursor of bio-fuels, such as 2,5-dimethylfuran (DMF) [20,21], 5-ethoxymethylfurfural (EMF) [22] and long chain alkanes [23]. In addition, it is possible to convert HMF into interesting monomers, such as 2,5-furandicarboxylic acid (FDCA) [24,25], 2,5-bis (hydroxymethyl)furan (BHMF) [26][27][28], 2,5-bis(hydroxymethyl)tetrahydrofuran (BHMTHF) [29][30][31] and caprolactone [32] and many more valuable products [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Undesirable high Brønsted acidity cause side reactions, [24,48, 55] such as etherification and acetalization with 2‐propanol as a solvent [35] . It was also observed that Brønsted acids in Co/Al‐Beta suppress the yield of DMF in HMF transformation [17] analogously as observed over Ru/C and sulphuric acid [59] . Weak acid sites determined by ammonia TPD were active and selective in HMF transformation to DMF over Ru/MoO x /C (Table 1, entry 21), while Ru/C exhibited no acidity [52] .…”
Section: Catalyst Selectionmentioning
confidence: 84%
“…[35] It was also observed that Brønsted acids in Co/Al-Beta suppress the yield of DMF in HMF transformation [17] analogously as observed over Ru/C and sulphuric acid. [59] Weak acid sites determined by ammonia TPD were active and selective in HMF transformation to DMF over Ru/MoO x /C ( Table 1, entry 21), while Ru/C exhibited no acidity. [52] As a comparison the main product was DHMTHF with the yield of 91 % over Ru/CeO x in HMF transformation at 130°C under 20 bar hydrogen in 1-butanol-water mixture as a solvent.…”
Section: Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a poisoning effect of H 2 SO 4 on Ru/C catalyst was observed by Gilkey et al in the hydrodeoxygenation of DMF via CTH in 2-propanol. [93] It is believed that the efficient ring-opening of furans to linear molecules requires a combination of metal and acid sites. However, severe suppression of metal chemistry was observed when having both Ru/C and H 2 SO 4 in the reaction system.…”
Section: Feedstock Impuritiesmentioning
confidence: 99%